Optimizing Academic Supervision by School Principals to Improve Elementary School Teacher Performance: A Systematic Literature Review - Respati Respati (Journal of Innovation in Teaching and Instructional Media, 2026)
This study analyzes and optimizes principal-led academic supervision to improve elementary teacher performance. A Systematic Literature Review (SLR) of 15 peer-reviewed articles (2021–2026) identifies four essential dimensions: (systematic planning aligned with teacher needs, clinical observation with collaborative feedback, sustained follow-up programs, and technology integration for efficiency and transparency. Key synthesized findings also reveal persistent barriers: principals’ excessive administrative loads and lack of specialized supervisory training. The novelty lies in an empirically-grounded optimization framework tailored specifically to primary school contexts. Practically, the results offer principals actionable strategies and provide education authorities a blueprint for targeted training programs. The contribution advances supervision theory by linking practices directly to teacher professional development and student learning outcomes in elementary schools.